Impact of Nutritional Education Intervention on Mothers Knowledge, Practices and Nutritional Status of Children Under-Five in Rural Mangaluru, Karnataka: A Quasi-experimental Pilot Study - Savitha Naik; Abhay Nirgude; Priya Reshma Arahna (Journal of Clinical and Diagnostic Research)
Introduction: Understanding the effectiveness of nutritional education interventions in rural settings is crucial for developing strategies to combat malnutrition and promote healthy growth in children. Enhancing mothers’ knowledge and practices can lead to better child health and development, and also contribute to more favourable long-term outcomes for both children and their communities. Aim: To implement a Nutrition Intervention Program (NIP) to enhance the nutritional status of children under-five by improving mothers’ knowledge and practices regarding child nutrition, thereby supporting the optimal growth and development of their children. Materials and Methods: A quasi-experimental study was conducted among parents of children under-five in the selected rural areas of Kukkuttu and Bhagambila, Mangaluru, Karnataka, India. The total sample size was 78 participants, with 39 in the intervention group and 39 in the control group. Data were collected using a structured knowledge questionnaire and an observational practice checklist. The parameters studied included height, weight, Mid-Upper Arm Circumference (MUAC), and the anthropometric indicators: weight for height, height for age, weight for age, and Body Mass Index (BMI) for age. These indicators are categorised based on growth and development standards established by the World Health Organisation (WHO). Epi Antro software was used to assess undernutrition, overnutrition and normal nutritional status among children under-five. Statistical analyses, including frequency, percentage, mean and standard deviation, multivariate ANOVA, two-factor repeated measures of ANOVA, Fisher’s exact test, Chi-square test, and post-hoc analysis, were used to analyse the data. Results: The mean age of the children under-five in the intervention group was 26.39±9.43 months and control group 22.74±10.65 months. The mean birth weight of the children in the intervention group was 2.75±0.28 kg and control group 2.64±0.27 kg. The mean birth order of the children in the intervention group was 2.02±1.15 and in the control group 3.10±1.75. There was a significant difference in parental knowledge scores within the groups (p-value=0.001, F=315.439) and between the groups (p-value=0.001, F=20.455). Parental practice scores also showed significant differences within the groups (p-value=0.001, F=333.897) and between the groups (p-value=0.001, F=196.446). There was a significant difference in stunting and underweight between the pretest and post-test (p-value <0.05) among children under-five. Conclusion: The study demonstrates that implementing a NIP effectively enhances mothers’ knowledge and practices related to child nutrition. Therefore, such interventions are valuable for promoting better health outcomes in children by educating and empowering mothers with the necessary knowledge and practices for optimal child nutrition.